Factors associated with adherence to Mediterranean diet among Saudi non-diabetic patients attending primary health care centers: A cross-sectional study. Issue 2 (April 2019) - Aljabri, Mydaa K.; Al-Raddadi, Rajaa; Bahijri, Suhad M.; Al Ahmadi, Jawaher; Ajabnoor, Ghada; Jambi, Hanan A.
الملخص: أهداف البحث: للتحقيق في العوامل المسؤولة ودرجة الالتزام بحمية البحر الأبيض المتوسط بين المرضى غير المصابين بالسكري من مراجعي مراكز الرعاية الصحية الأولية. طرق البحث: أُجريت دراسة مستعرضة في مراكز الرعاية الصحية الأولية بجدة، بواسطة استبانة مصدقة ذاتية الاستخدام، تقوم بتقييم مستويات الالتزام لـ ١٤ جانبا غذائيا متعلقا بحمية البحر الأبيض المتوسط. تمكِّن الاستبانة من حساب درجة التزام (٠- ١٤)، في حين تم افتراض التزام غير كافي للنتائج ≥٧. وقد شملت عوامل الالتزام الخصائص الديموغرافية الاجتماعية العامة والتاريخ المَرَضي ونمط الحياة وعوامل الخطورة القلبية الوعائية مثل مؤشر كتلة الجسم ونسبة الخصر إلى الورك وضغط الدم والصيام ومستوى الجلوكوز في الدم بعد الأكل بساعة واحدة. النتائج: من بين المشاركين الـ ٢٦٥ (٥٠.٦٪ ذكورا)، سُجِّل عدم الالتزام الكافي في ٧٤.٣٪. وكانت درجات الالتزام أعلى في المشاركين المتزوجين (٦.٨٦ ± ١.٧٤مقابل ٦.٢٤ ± ١.٧٩) والممارسين للنشاط البدني المنتظم (٦.٧٩ ± ١.٩٠مقابل ٦.٣٠ ± ١.٦٣) بالمقارنة مع نظرائهم، على التوالي. علاوة على ذلك، فقد ازداد الالتزام بالحمية المتوسطية مع التقدم في العمر (معامل انحدار غير معياري=٠.٠٢ ومعامل ارتباط= ٠.١٣٣). ومن المثير للاهتمام، أنه لم ترتبط درجات الالتزام بعوامل الخطورة الرئيسة المتعلقة بالقلب والأوعية الدموية، فيما عدا الارتفاع البيّن في ضغط الدم الانبساطي بين المشاركين الملتزمين مقارنة بقرنائهم قليلي الالتزام (٧٧.٩٦± ١٢.٢٠مقابل ٧٤.٠١± ١٢.٢٤، على التوالي). الاستنتاجات: كان لواحد من أصل ٤ مرضى غير مصابين بداء السكري من الذين راجعوا مراكز الرعاية الصحية الأولية، التزام جيد بحمية البحر الأبيض المتوسط دون ارتباط يُذكر بعوامل الخطورة القلبية الوعائية. يُوصى بإجراء المزيد من الدراسات للتحقيق في الوعي والمعرفة حول النظام الغذائي المتوسطي بين السكان السعوديين، ومن بعدها يمكن تفصيل برامج التوعية وفقًا لذلك. Abstract: Objectives: To investigate the degree and factors responsible for adherence to a Mediterranean diet among non-diabetic patients attending primary health care centres (PHCCs). Methods: A cross-sectional study was conducted in Jeddah PHCCs using a validated self-administered questionnaire which assessed adherence levels to 14 dietary aspects related to the Mediterranean diet. The questionnaire enabled calculation of an adherence score (0–14), where inadequate adherence was assumed for scores ≤7. Factors of adherence included general socio-demographic characteristics, medical history, lifestyle, and cardiovascular risk factors such as body mass index, waist-to-hip ratio, blood pressure, and fasting and 1-h postprandial blood glucose levels. Results: Of the 265 participants (50.6% males), inadequate adherence was reported in 74.3%. Adherence scores were higher in married participants than in unmarried ones (6.68 ± 1.74 vs. 6.24 ± 1.79, p = 0.04), as well as in those who engaged in regular physical activity vs. those who did not (6.79 ± 1.90 vs. 6.30 ± 1.63, p = 0.02). Furthermore, Mediterranean diet adherence increased with age (B = 0.02, r = 0.133; p  < 0.001). Interestingly, adherence scores were not associated with major cardiovascular risk factors except for a significantly higher diastolic blood pressure in participants with adequate as opposed to low adherence (77.96 ± 12.20 vs. 74.01 ± 12.24, respectively, p  = 0.022). Conclusion: One out of 4 non-diabetic patients attending PHCCs exhibited good adherence to a Mediterranean diet without considerable association with cardiovascular risk factors. Further studies are recommended to investigate awareness and knowledge regarding the Mediterranean diet among Saudi populations. Subsequently, awareness programs could be tailored accordingly.